Indications and rates of lower segment caesarean section at tertiary care hospital - an analytical study - Jawa, Ashmita; Garg, Swati; Tater, Arihant; Sharma, Urvashi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Over the past few decades, there has been a rise in the rates of caesarean section globally. The reasons for this are multifactorial including changes in women’s preferences, a growing number who have previously had a caesarean delivery and technological advances which aid in early identification of a compromised fetus. Methods: This study aims to analyze the rates and indications of lower segment caesarean section (LSCS) in our institution. This retrospective study was conducted over a period of six months - December 2015 to May 2016 at Mahatma Gandhi Medical College and Hospital, Jaipur. Total number of patients who delivered in our hospital during the defined study period was recorded and a statistical analysis of various parameters was done. Results: The total number of women delivered over the study period was 1645, out of which caesarean sections (CS) were 523. The overall CS rate calculated was 31.8%. Previous LSCS was the leading indication to the CS rate. Conclusions: Individualization of the indication and obstetric audits can help in reducing both maternal and peri-natal morbidity and mortality.